2022
DOI: 10.3390/ijms232213902
|View full text |Cite
|
Sign up to set email alerts
|

Oncometabolism: A Paradigm for the Metabolic Remodeling of the Failing Heart

Abstract: Heart failure is associated with profound alterations in cardiac intermediary metabolism. One of the prevailing hypotheses is that metabolic remodeling leads to a mismatch between cardiac energy (ATP) production and demand, thereby impairing cardiac function. However, even after decades of research, the relevance of metabolic remodeling in the pathogenesis of heart failure has remained elusive. Here we propose that cardiac metabolic remodeling should be looked upon from more perspectives than the mere producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 216 publications
0
6
0
Order By: Relevance
“…The majority of ATP in the healthy heart is derived from mitochondrial oxidative metabolism, whereas the end-stage failing heart undergoes a drastic shift in energy metabolism. Van Bilsen et al proposed that in the initiation of HF, myocardial fatty acid, glucose, ketone body, and branched-chain amino acid metabolism is disturbed, leading to alterations in myocardial structure and function 26 , 40 . Moreover, metabolic disturbances contribute to the disruption of mitochondrial morphology and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of ATP in the healthy heart is derived from mitochondrial oxidative metabolism, whereas the end-stage failing heart undergoes a drastic shift in energy metabolism. Van Bilsen et al proposed that in the initiation of HF, myocardial fatty acid, glucose, ketone body, and branched-chain amino acid metabolism is disturbed, leading to alterations in myocardial structure and function 26 , 40 . Moreover, metabolic disturbances contribute to the disruption of mitochondrial morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ECM plays an important role in pressure overload-induced heart failure, and excessive deposition of ECM proteins leads to fibrosis and deterioration of cardiac function 25 . Similarly, cell migration is crucial for fibrosis, with myofibroblasts under pressure overload conditions in HF showing enhanced migration abilities, secreting ECM proteins, and leading to myocardial remodeling and stiffening, thereby impairing cardiac function 26 . In addition, increased endothelial cell proliferation and promotion of angiogenesis significantly improve cardiac function in pressure overload-induced myocardial remodeling 27 .…”
Section: Sema Reverses Pathological Myocardial Remodeling Induced By Tacmentioning
confidence: 99%
“…Mitochondrial metabolic reprogramming is a distinctive characteristic of cardiac cells and occurs as a consequence of adaptation or maladaptation to the environmental stress ( 22 , 23 ). In a healthy heart, mitochondrial oxidative metabolism provides ATP and precursors for macromolecular biosynthesis to meet the energy requirements for cardiac cell survival ( 24 , 25 ). The predominant mechanisms of cardiac damage are the defects in OXPHOS capacity and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The inability of Fgf15 ‐null mice to orchestrate a proper cardiac hypertrophy response might be seen as a detrimental event for the myocardium rather than a protective one based on our echocardiographic data indicating diastolic dysfunction with preserved ejection fraction in Fgf15 ‐null mice, a phenotype resembling heart failure with preserved ejection fraction (HFpEF) [37]. In agreement with this, the increased levels of atrial natriuretic peptide observed in Fgf15 ‐null mice also point towards a pathological phenotype similar to the one found in cardiac atrophy models where the levels of natriuretic peptides are also induced [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Independently of the hypertrophic model used, we found that the genes involved in fatty acid oxidation are reduced in Fgf15 ‐null mice and are increased after FGF15 overexpression, which suggests the involvement of FGF15/19 in the control of cardiac metabolism. Although hypertrophy is usually associated with reduced fatty acid metabolism and increased cardiac glucose uptake, under certain hypertrophic circumstances such as a high‐fat diet or pregnancy, the heart is forced to rely even more on fatty acid oxidation [37]. In fact, recent findings point to the metabolic inflexibility of the heart as the hallmark for cardiac hypertrophy development rather than the switch from fatty acid to glucose metabolism [47].…”
Section: Discussionmentioning
confidence: 99%